The effects of fatigue on soccer skills performed during a soccer match simulation - Russell, M.; Benton, D.; Kingsley, M. I. C. (International Journal of Sports Physiology and Performance, 2011)
Purpose: This study examined the effects of exercise-induced fatigue on soccer skills performed throughout simulated match play. Methods: Fifteen academy soccer players completed a soccer match simulation (SMS) including passing, dribbling, and shooting skills. Precision, success rate, and ball speed were determined via video analysis for all skills. Blood samples were obtained before exercise (preexercise), every 15 min during the simulation (15, 30, 45, 60, 75, and 90 min), and 10 min into half-time. Results: Preliminary testing confirmed test-retest repeatability of performance, physiological, and metabolic responses to 45 min of the SMS. Exercise influenced shooting precision (timing effect: P = .035) and passing speed (timing effect: P = .011), such that shots taken after exercise were 25.5 ± 4.0% less accurate than those taken before exercise and passes in the last 15 min were 7.8 ± 4.3% slower than in the first 15 min. Shot and pass speeds were slower during the second half compared with the first half (shooting: 17.3 ± 0.3 m/s vs 16.6 ± 0.3 m/s, P = 0.012; passing: 13.0 ± 0.5 m/s vs 12.2 ± 0.5 m/s, P = 0.039). Dribbling performance was unaffected by exercise. Blood lactate concentrations were elevated above preexercise values throughout exercise (time of sample effect: P < .001). Conclusions: These findings demonstrate that soccer-specific exercise influenced the quality of performance in gross motor skills, such as passing and shooting. Therefore, interventions to maintain skilled performance during the second half of soccer match play are warranted.